Magnetic defluorination adsorption material and preparation method thereof

By preparing black granular magnetic fluorine-removing adsorption materials with particle sizes of 0.1-10μm, the existing fluorine-removing technology has been solved, and the fluorine ion adsorption effect is achieved with high efficiency, high cost and great environmental impact, and the fluorine ion adsorption effect is achieved with the advantages of rapid recovery.

CN119500055APending Publication Date: 2025-02-25JIANGXI COPPER TECHNOLOGY RESEARCH INSTITUTE CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411592535.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-08
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing fluorine removal technology has problems such as low efficiency, high cost and great environmental impact, and it is difficult to effectively remove excessive fluorine in water, affecting the environment and human health.

Method used

A black particle magnetic fluorine-removing adsorption material with a particle size of 0.1-10 μm is used, which is coated on the surface of the alumina by lanthanum oxide. The material is prepared by a specific preparation method, including the use of a magnetic particle suspension and mixed liquid B, followed by oxidation and calcination and grinding treatment to obtain a magnetic fluorine-removing adsorption material with a high specific surface area and a high fluorine-adsorption capacity.

Benefits of technology

It has achieved efficient adsorption of fluoride ions, with an adsorption capacity greater than 75.00 mg/g, and the material has a magnetic framework, which can be quickly recovered, reducing costs and environmental impacts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500055A_ABST
    Figure CN119500055A_ABST
Patent Text Reader

Abstract

The invention discloses a magnetic defluorination adsorption material and a preparation method thereof. The magnetic defluorination adsorption material is a black particle with a particle size of 0.1-10 [mu] m. The lanthanum oxide with the cloud sheet-shaped nano structure is coated on the surface of the aluminum oxide. The preparation method comprises the following steps: preparing a magnetic particle suspension by taking ferrous salt and ferric salt as raw materials; dissolving a certain amount of Al (NO3) 3 and LaCl3 to obtain a mixed solution B, mixing the mixed solution B with the magnetic particle suspension, and reacting to obtain a magnetic defluorination adsorption material precursor; and performing oxidizing roasting on the magnetic defluorination adsorption material precursor in an air atmosphere, grinding by using a mortar after roasting, washing by using deionized water, and performing solid-liquid separation by using a magnet to obtain the magnetic defluorination adsorption material. The adsorption material disclosed by the invention has the characteristics of large adsorption capacity, low adsorbent loss, safe water quality after treatment, easiness in recovery and regeneration and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a magnetic defluorination adsorption material and a preparation method thereof. Background Art

[0002] Excessive fluoride is a serious hazard to the environment and human health. Excessive fluoride in water can cause water pollution, affect the living environment of aquatic organisms, and may cause excessive fluoride content in drinking water, which in turn endangers human health. Long-term drinking of water with excessive fluoride may cause health problems such as bone disease, tooth discoloration and organ dysfunction, especially for children and pregnant women. Therefore, it is very important to control and remove the fluoride content in water.

[0003] Traditional fluorine removal methods include chemical precipitation and reverse osmosis. Although the chemical precipitation method is simple and easy to use, it has a large amount of sediment residue. It is often difficult to meet the emission standards when used alone and requires further deep treatment. The reverse osmosis method is highly efficient, but the operating cost is high and it is not suitable for large-scale applications. In contrast, the adsorption method, as a feasible fluorine removal technology, has the advantages of simple operation, no need for large energy input, continuous operation, and easy treatment of waste generated after treatment. By rationally designing magnetic adsorption materials, not only can the fluorine adsorption efficiency be improved, but also the recycling of materials can be achieved, costs can be reduced, and the impact on the environment can be reduced. Therefore, it has broad application prospects in fluorine removal technology. Summary of the invention

[0004] The invention discloses a magnetic defluorination adsorption material and a preparation method thereof, so as to solve any of the above and other potential problems in the prior art.

[0005] In order to solve the above technical problems, the technical solution provided by the present invention is: a magnetic defluorination adsorption material, the magnetic defluorination adsorption material is in the form of black particles with a particle size of 0.1-10 μm;

[0006] Cloud-like nanostructured lanthanum oxide is coated on the surface of aluminum oxide.

[0007] Another object of the present invention is to provide a method for preparing the above-mentioned magnetic defluorination adsorption material, which specifically comprises the following steps:

[0008] S1) preparing a magnetic particle suspension using a divalent iron salt and a trivalent iron salt as raw materials;

[0009] S2) dissolving a certain amount of Al(NO3)3 and LaCl3 to obtain a mixed solution B, and then mixing it with the magnetic particle suspension of S1), and after reaction, obtaining a magnetic defluorination adsorption material precursor;

[0010] S3) oxidizing and calcining the magnetic defluorination adsorption material precursor in an air atmosphere, grinding it with a mortar and then washing it with deionized water, and performing solid-liquid separation with a magnet to obtain the magnetic defluorination adsorption material.

[0011] Further, the specific steps of S1) are:

[0012] S1.1) using deionized water degassed with N2 to dissolve Fe(NO3)2 and Fe(NO3)3 to prepare a mixed solution A;

[0013] S1.2) The mixed solution A obtained in S1.1) is dripped into an alkaline solution with a certain pH value at a certain rate, and N2 is introduced to isolate the air, and a water bath heating reaction is carried out. After the reaction is completed, the obtained magnetic particles are separated by a magnet to obtain a magnetic particle suspension.

[0014] Further, the mixed solution A in S1.1) has a concentration of 70-75 g / L of Fe(NO3)2 and a concentration of 160-180 g / L of Fe(NO3)3;

[0015] Furthermore, the dripping rate of the mixed solution A in S1.2) is 2-5 mL / min, the pH of the alkali solution is 13-14, and the water bath heating temperature is 75-85°C.

[0016] Further, the specific steps in S2) are:

[0017] S2.1) dissolving Al(NO3)3 and LaCl3 in deionized water to prepare a mixed solution B;

[0018] S2.2) dropping the mixed solution B obtained in S2.1) into the magnetic particle suspension at a certain rate, stirring slowly with a non-magnetic stirrer, heating in a water bath for reaction, and adjusting the pH value with alkaline solution after all the mixed solution B has been dropped, and reacting at a constant temperature for three hours;

[0019] S2.3) After the reaction is completed, the obtained magnetic material is separated by a magnet and rinsed with deionized water to obtain a magnetic defluorination adsorption material precursor.

[0020] Furthermore, the mixed solution B in S2.1) has an Al(NO3)3 concentration of 200-240 g / L and a LaCl3 concentration of 120-140 g / L.

[0021] Further, the mixed solution B in S2.2) is added at a rate of 10-20 mL / min, and Al 3+ The mass of the magnetic particles is 0.7-1.1 times the mass of the magnetic particles. 3+ The mass of Al 3+The mass is 2.4-3.4 times, the water bath heating temperature is 80-85°C, and the pH value of the system is adjusted to 8-9.

[0022] Furthermore, the oxidation roasting temperature in S3) is 280-320°C, and the roasting time is 1-2h.

[0023] Furthermore, the magnetic defluorination material prepared by the method has a specific surface area greater than 20.00 m 2 / g, and the adsorption capacity is greater than 75.00 mg / g.

[0024] Due to the adoption of the above scheme, the present invention has the following characteristics: the magnetic defluorination adsorbent material prepared by the present invention has a small particle size, is easy to disperse, and can efficiently adsorb fluoride ions. At the same time, the adsorbent has a magnetic skeleton and can use a magnetic field to quickly recover the adsorbent material.

[0025] The magnetic defluorination adsorption material (Fe3O4-Al2O3-La2O3) prepared by the present invention has a surface morphology of the adsorbent, and the cloud-like flake nanostructure is mainly composed of lanthanum oxide, which covers the surface of aluminum oxide. The specific surface area of ​​the magnetic defluorination material is greater than 20.00 m 2 / g, and has many fluorine binding sites, and its adsorption capacity is greater than 75.00 mg / g. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 This is a schematic diagram of an overall scanning electron microscope image of a magnetic defluorination adsorption material obtained by using Example 1 of the preparation method of the present invention.

[0027] Figure 2 This is a schematic diagram of a local scanning electron microscope image of a magnetic defluorination adsorbent material obtained by Example 1 of the preparation method of the present invention.

[0028] Figure 3 It is a schematic diagram of the defluorination effect curve of the magnetic defluorination adsorption material of the present invention. DETAILED DESCRIPTION

[0029] The principles and features of the present invention are described below in conjunction with specific embodiments. The examples given are only used to introduce the present invention and are not used to limit the scope of the present invention.

[0030] Example 1

[0031] A method for preparing a magnetic defluorination adsorption material is as follows:

[0032] A mixed solution A of 70 g / L Fe(NO3)2 and 160 g / L Fe(NO3)3 was prepared using deionized water degassed with N2.

[0033] Mixed solution A was added dropwise into a sodium hydroxide solution with a pH value of 13 at a rate of 2 mL / min. The process required vigorous stirring with a non-magnetic stirrer, while N2 was introduced to isolate the air, and the mixture was heated to 75°C in a water bath for reaction.

[0034] After all the mixed solution A was dropped into the alkaline solution and reacted for 5 minutes, the obtained magnetic particles were separated by a magnet and rinsed with deionized water for 3 times.

[0035] Deionized water was used to prepare a mixed solution B containing 240 g / L Al(NO3)3 and 120 g / L LaCl3.

[0036] Mixed solution B was dripped into the magnetic particle suspension at a rate of 10 mL / min. 3+ The mass of the magnetic particles is 0.8 times the mass of the magnetic particles. 3+ The mass of Al 3+ The mixture was stirred slowly with a non-magnetic stirrer, and after all the mixed solution B was dropped in, the pH value was adjusted to 8.5 with sodium hydroxide solution, and the mixture was reacted at a constant temperature of 85°C in a water bath for three hours.

[0037] After the reaction is completed, the obtained magnetic material is separated by a magnet and washed with deionized water to obtain a magnetic defluorination adsorption material precursor.

[0038] The magnetic defluorination adsorption material precursor was oxidatively calcined at 280°C for 2h in an air atmosphere, ground with a mortar after calcination, and then rinsed with deionized water. The magnetic defluorination adsorption material was obtained by solid-liquid separation using a magnet. The overall and local electron microscope images of the magnetic defluorination adsorption material are as follows: Figure 1 and Figure 2 The specific surface area of ​​the magnetic defluorination adsorption material is 20.21m 2 / g, and the adsorption capacity is 75.68mg / g.

[0039] Example 2

[0040] A method for preparing a magnetic defluorination adsorption material is as follows:

[0041] A mixed solution A of 75 g / L Fe(NO3)2 and 175 g / L Fe(NO3)3 was prepared using deionized water degassed with N2.

[0042] Mixed solution A was added dropwise into a sodium hydroxide solution with a pH value of 14 at a rate of 5 mL / min. The process required vigorous stirring with a non-magnetic stirrer, while N2 was introduced to isolate the air, and the mixture was heated to 85°C in a water bath for reaction.

[0043] After all the mixed solution A was dropped into the alkaline solution and reacted for 10 minutes, the obtained magnetic particles were separated by a magnet and rinsed with deionized water for 3 times.

[0044] Deionized water was used to prepare a mixed solution B containing 200 g / L Al(NO3)3 and 140 g / L LaCl3.

[0045] Mixed solution B was dripped into the magnetic particle suspension at a rate of 20 mL / min. 3+ The mass of the magnetic particles is 1.1 times the mass of the magnetic particles. 3+ The mass of Al 3+ The mixture was added with a non-magnetic stirrer and the pH value was adjusted to 8.0 using sodium hydroxide solution after all the mixed solution B was dropped in. The mixture was reacted at a constant temperature of 80°C in a water bath for three hours.

[0046] After the reaction is completed, the obtained magnetic material is separated by a magnet and washed with deionized water to obtain a magnetic defluorination adsorption material precursor.

[0047] The magnetic defluorination adsorption material precursor was oxidatively calcined at 320°C for 1 hour in an air atmosphere, ground with a mortar after calcination, rinsed with deionized water, and separated into solid and liquid using a magnet to obtain a magnetic defluorination adsorption material. The magnetic defluorination adsorption material has a specific surface area of ​​20.52m2 / g and an adsorption capacity of 77.36mg / g.

[0048] The magnetic defluorination adsorption material involved in the present invention is an adsorbent made from low-cost iron and aluminum as basic raw materials and modified by rare earth element lanthanum. It is a black granular material with a particle size between 0.1-10 μm.

[0049] The adsorbent of the present invention has the characteristics of large adsorption capacity, safety, high efficiency, and easy recycling and regeneration. The actual operation shows that for 20 mg / L fluoride-containing wastewater (pH is about 7.32), its treatment effect is as follows: Figure 3 As shown, the adsorbent can achieve a fluoride ion concentration of less than 1 mg / L within 15 minutes, and its adsorption capacity can reach 77.36 mg / g. The adsorbent involved in the present invention will not have the problem of excessive aluminum ions during use.

[0050] The above is a detailed introduction to a magnetic defluorination adsorption material and a preparation method thereof provided in the embodiments of the present application. The description of the above embodiments is only used to help understand the method and its core idea of ​​the present application; at the same time, for a person skilled in the art, according to the idea of ​​the present application, there will be changes in the specific implementation method and application scope. In summary, the content of this specification should not be understood as a limitation on the present application.

[0051] For example, certain words are used in the specification and claims to refer to specific components. Those skilled in the art should understand that hardware manufacturers may use different terms to refer to the same component. This specification and claims do not use differences in names as a way to distinguish components, but use differences in components' functions as the criteria for distinction. For example, "including" and "comprising" mentioned throughout the specification and claims are open-ended terms and should be interpreted as "including / including but not limited to".

[0052] "Approximately" means that within an acceptable error range, those skilled in the art can solve the technical problem within a certain error range and basically achieve the technical effect. The subsequent description of the specification is a preferred embodiment of the present application, but the description is for the purpose of illustrating the general principles of the present application and is not intended to limit the scope of the present application. The scope of protection of the present application shall be determined by the definition of the attached claims.

[0053] It should also be noted that the terms "include", "comprises" or any other variations thereof are intended to cover non-exclusive inclusion, so that a product or system including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such a product or system. In the absence of more restrictions, the elements defined by the sentence "comprises a ..." do not exclude the existence of other identical elements in the product or system including the elements.

[0054] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0055] The above description shows and describes several preferred embodiments of the present application, but as mentioned above, it should be understood that the present application is not limited to the form disclosed herein, and should not be regarded as excluding other embodiments, but can be used in various other combinations, modifications and environments, and can be modified within the scope of the application concept described herein through the above teachings or the technology or knowledge of the relevant field. The changes and modifications made by those skilled in the art do not deviate from the spirit and scope of the present application, and should be within the scope of protection of the claims attached to the present application.

Claims

1. A magnetic defluorination adsorption material, characterized in that: The magnetic defluorination adsorption material is in the form of black particles with a particle size of 0.1-10 μm; Cloud-like nanostructured lanthanum oxide is coated on the surface of aluminum oxide.

2. A method for preparing the magnetic defluorination adsorption material according to claim 1, characterized in that: The method specifically comprises the following steps: S1) preparing a magnetic particle suspension using a divalent iron salt and a trivalent iron salt as raw materials; S2) dissolving a certain amount of Al(NO3)3 and LaCl3 to obtain a mixed solution B, and then mixing it with the magnetic particle suspension of S1), and after reaction, obtaining a magnetic defluorination adsorption material precursor; S3) oxidizing and calcining the magnetic defluorination adsorption material precursor in an air atmosphere, grinding it with a mortar and then washing it with deionized water, and performing solid-liquid separation with a magnet to obtain the magnetic defluorination adsorption material.

3. The method according to claim 2, characterized in that The specific steps of S1) are: S1.1) using deionized water degassed with N2 to dissolve Fe(NO3)2 and Fe(NO3)3 to prepare a mixed solution A; S1.2) The mixed solution A obtained in S1.1) is dripped into an alkaline solution with a certain pH value at a certain rate, and N2 is introduced to isolate the air, and a water bath heating reaction is carried out. After the reaction is completed, the obtained magnetic particles are separated by a magnet to obtain a magnetic particle suspension.

4. The method according to claim 3, characterized in that The mixed solution A in S1.1) has a Fe(NO3)2 concentration of 70-75 g / L and a Fe(NO3)3 concentration of 160-180 g / L.

5. The method according to claim 3, characterized in that: The drop-in rate of the mixed solution A in S1.2) is 2-5 mL / min, the pH of the alkali solution is 13-14, and the water bath heating temperature is 75-85°C.

6. The method according to claim 2, characterized in that The specific steps in S2) are: S2.1) dissolving Al(NO3)3 and LaCl3 in deionized water to prepare a mixed solution B; S2.2) dropping the mixed solution B obtained in S2.1) into the magnetic particle suspension at a certain rate, stirring slowly with a non-magnetic stirrer, heating in a water bath for reaction, adjusting the pH value with alkaline solution after all the mixed solution B has been dropped, and reacting at a constant temperature for at least 3 hours; S2.3) After the reaction is completed, the obtained magnetic material is separated by a magnet and rinsed with deionized water to obtain a magnetic defluorination adsorption material precursor.

7. The method according to claim 6, characterized in that The mixed solution B in S2.1) has an Al(NO3)3 concentration of 200-240 g / L and a LaCl3 concentration of 120-140 g / L.

8. The method according to claim 6, characterized in that The mixed solution B in S2.2) is added at a rate of 10-20 mL / min. 3+ The mass of the magnetic particles is 0.7-1.1 times the mass of the magnetic particles. 3+ The mass of Al 3+ The mass is 2.4-3.4 times, the water bath heating temperature is 80-85°C, and the pH value of the system is adjusted to 8-9.

9. The method according to claim 2, characterized in that: The oxidation roasting temperature in S3) is 280-320°C, and the roasting time is 1-2h.

10. The method according to claim 2, characterized in that The specific surface area of ​​the magnetic defluorination material prepared by the method is greater than 20.00 m 2 / g, and the adsorption capacity is greater than 75.00 mg / g.